Composite phase change materials with good reversible thermochromic ability in delignified wood substrate for thermal energy storage. (15th February 2018) - Yang, Haiyue; Wang, Yazhou; Yu, Qianqian; Cao, Guoliang; Yang, Rue; Ke, Jiaona; Di, Xin; Liu, Feng; Zhang, Wenbo; Wang, Chengyu
Graphical abstract: Highlights: Delignified wood as supporting material is firstly used in composite phase change materials. Reversible thermochromic ability visibly shows phase change process by color change. Low thermal conductivity of TCDWs can maintain internal temperature for longer time. Abstract: Phase change materials applied in the thermal insulation of building or storage system are beneficial to slow down internal temperature fluctuation and decrease energy consumption. Visible temperature change can provide convenience for people's production and life. In this work, the thermochromic delignified wood composite phase change materials (TCDWs) composed of thermochromic (TC) compound and delignified wood (DW) are fabricated by vacuum-assisted impregnation method. Various techniques are applied to characterize mechanical and thermal properties of TCDWs. Results indicate that TCDWs exhibit suitable phase change temperature, large latent heat, good thermal reliability, as well as excellent thermal stability and mechanical properties. More importantly, TCDWs have excellent reversible thermochromic ability and visibly show the phase change progress and temperature by color change from dark blue to off-white. The thermal insulation ability of TCDWs can reduce heat flow and heat exchange between inside and outside environment, maintaining the internal temperature for longer time. The largest absorption capacity of DW is 65%, which is 15% more than that of pristine wood (PW). The excellent reversible thermochromic, thermal and mechanical properties of TCDWs have great potential in thermal energy storage applications including thermal insulation, decoration, furniture, storage and building energy conservation.